Decarbonization technologies for the reduction of CO2 emissions in multifamily buildings - Carlos Magno Chavarry Vallejos; Jose del Carmen Zavala Loria; Marco Antonio Rojo Gutierrez (Universidad Ciencia y Tecnología, 2023)
This paper analyzed decarbonization technologies that reduce carbon dioxide emissions in multifamily buildings. The research method is deductive, quantitative approach, applied orientation, descriptive, correlational, and explanatory. The design is non-experimental, cross-sectional, and prospective. The results show that the reduction of carbon dioxide emissions using decarbonization technologies in housing projects is higher in terms of electrification and the use of biomass in materials modeling. At the same time, they are considerably lower in terms of energy efficiency and renewable energy. Finally, it was found that reducing carbon dioxide in multifamily housing contributes significantly to the economy and contributes to national and international environmental improvements, creating increasingly healthy spaces.